An environmental quality management scheme for Canlubang New City - Gemanil, Editha M. (1977, 1977)
The environmental quality management of a project area like the Canlubang New City encompasses a big sphere of activity. This may be basically defined as an influencing of human activities as they affect the quality of mankind's physical environment especially the air, water and terrestrial features. This environmental management takes sanitary engineering, environmental health, urban and regional planing and public administration in totality. The concern of this study is to encompass overall environmental quality management planning; considering that environment has a four-fold implication. The first concept considers all natural aspects of the environment like air, noise, sewage, solid wastes, toxic substances, and water. The second definition however, encompasses energy, historical preservation, land use, open space, radiation, population and wildlife preservation; while the third implication covers aesthetics, health, housing, mass transportation, recreation, streets and housing. The fourth implication being the broader is also of relevance to this research study, which considers economic development, education, employment, public safety and welfare. These concepts are conceived in the proposed environmental quality management of the Canlubang New City.
One of the objectives behind the development of the Canlubang New City is to minimize the problems that beset Metropolitan Manila Area like high rate of population growth, underemployment/unemployment, low standards of living and the most relevant aspect - environmental degradation. In the planning of Metropolitan Manila, the protection of the environment was not pre-conceived; hence, different environmental problems are increasingly felt in Metro Manila. This aspect on environmental quality is of prime consideration in the planning and development of Canlubang New City. The air, water and solid waste management is given considerable attention a t this early stage, because it deemed necessary to establish adequate environmental protection and control measures at this stage of development rather than control the problem when it is already existing. The other plans to supplement Metropolitan Manila expansion are discussed in the first chapter, while the second chapter presents the overall framework plan and the present existing conditions in the estate. Chapters 4 to 5 contain the author's projections, research and development results of different ways and means of reuse/recycle of agricultural waste products, plus the recommendations/proposals she feels are necessary and relevant in the environmental quality management of the new city.
Appendix A-E: leaves 86-131.
Photocopy.
Thesis (M.S. Environmental Engineering)--University of the Philippines Diliman.
Keywords: Environmental engineering; Canlubang New City